Strategy for Improving the Welfare of ASN PPPK Ministry of Religion during Retirement - Amin, Muhammad; Karbila, Ibnu Hasan; Nopilia, Leni (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This article examines that welfare and placement of retired Government Employees with Work Agreements (PPPK) at the Ministry of Religion. With the enactment of Law Number 20 of 2023, which regulates the rights of ASN, including PPPK, this study aims to evaluate the welfare conditions of PPPK retirees as well as the challenges and opportunities in their placement. The research method used is a case study and documentation analysis. The results of the study indicate that although PPPK are entitled to pension insurance, there are still several obstacles in its implementation, such as a lack of access to health services and training programs. The recommendations from this study are the need to increase pension benefits, provide comprehensive health insurance, and develop training programs to improve the welfare of retired PPPK.